Ответы и объяснения

2013-04-18T14:49:08+04:00

3)

а2=а1+d

а5=а1+4*d

 

а3=а1+2*d

а7=а1+6*d

 

 a2-a5=15

a1+d-a1-4d=15

-3d=15

d=-5

 

a3+a7=-6

a1+2d+a1+6d=-6

2a1=-6-8d=-6+40=34/2=17

 

а3=а1+2*d=17-10=7

а4=а1+3*d=17-15=2

 

4) \sqrt{x-1}=b1\\ \sqrt{6-x}=b2=b1*q\\ \sqrt{10+3x}=b3=b1*q^2\\ \sqrt{x-1}*q=\sqrt{6-x}\\</p>&#10;<p>\sqrt{6-x}*q=\sqrt{10+3x}\\ \sqrt{10+3x}*\sqrt{x-1}=\sqrt{6-x}*\sqrt{6-x}\\ x<=6 x>=1 x>=-10/3 1<=x<=6 (10+3x)(x-1)=(6-x)(6-x)\\ 10x+3x^2-10-3x=36-12x+x^2\\ 2x^2+19x-46=0\\ D= 361+368=729 = 27^2\\ x1=(-19+27)/4 \\ x=2

 

5)

10<=n*5+4<=99

1,2<=n<=19

 

 

a1=2*5+4=14

a3=3*5+4=19

A18=19*5+4=99

 

S=(a1+a18)*18/2=(14+99)*9=1017